A high-loading composite iodine positive electrode based on MXene electrochemical reaction regulator, and a preparation method and application thereof

CN119601570BActive Publication Date: 2026-10-16SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411624044.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2026-10-16
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

然而,对于锌碘电池的实用化研究依旧很欠缺

Benefits of technology

(1)本发明所制备的高载量复合碘正极能够有效地抑制多碘化物的穿梭效应以及提高碘转化反应动力学;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601570B_ABST
    Figure CN119601570B_ABST
Patent Text Reader

Abstract

The present application relates to a high-loading composite iodine positive electrode based on MXene electrochemical reaction regulator, and a preparation method and application thereof. The high-loading composite iodine positive electrode comprises: a porous self-supporting composite electrode film in which MXene nanosheets, carbon materials and cellulose are mixed to form a MXene / cellulose network to wrap the carbon materials, and an iodine active substance loaded on the porous self-supporting composite electrode film; wherein the iodine active substance comprises I ‑ ions and I2; the MXene nanosheets are at least one of Ti3C2T x , Nb2CT x , Mo2CT x and V2CT x .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of zinc-ion battery technology, specifically relating to a method for preparing a high-load zinc-iodine battery cathode, and more particularly to a high-load composite iodine cathode based on MXene electrochemical reaction regulator, its preparation method, and its application. Background Technology

[0002] Zinc-iodine (Zn-I2) batteries benefit from the abundance of their raw materials (55 μg / L in seawater). -1 ), and a relatively high discharge voltage (1.38V vs. Zn / Zn). 2+ ) and a high theoretical specific capacity (I2 / I - 211mAh g -1 Zinc-iodine batteries are among the most promising aqueous batteries currently available. However, they face significant challenges in Zn anode and I2 cathode technologies. Firstly, during charge and discharge, mild aqueous zinc-ion batteries inevitably experience dendrite growth, hydrogen evolution, and corrosion at the anode, severely limiting battery performance. Regarding the cathode, the I2 / I... - The conversion during battery cycling will form water-soluble polyiodides (I3). - I5 - Polyiodides tend to migrate to the zinc anode and react chemically with metallic zinc, which consumes active zinc and exacerbates battery degradation. Therefore, simultaneously addressing the issues of poor zinc reversibility and the polyiodide shuttle effect is crucial for the development of advanced zinc-iodine batteries.

[0003] Despite significant progress in addressing polyiodide shuttle and improving the reversibility of zinc anodes through strategies such as developing novel iodine-loaded cathodes, modifying separators, or adding electrolyte additives, practical research on zinc-iodine batteries remains lacking. On the one hand, to minimize the polyiodide shuttle effect, researchers have kept the active iodine content and iodine loading of the I2 electrode relatively low, typically below 15 mg / cm³. -2 This will result in a specific capacity of less than 2 mAh cm⁻¹. -2 This is significantly lower than the typical value for commercial lithium-ion batteries (3mAh cm⁻¹). -2 The high iodine content of zinc-iodine batteries has limited their practical application. On the other hand, to ensure long-term cycle stability, the utilization rate of the zinc anode is often very low to compensate for irreversible zinc loss during cycling. However, a significantly excessive zinc anode severely reduces the overall energy density of the battery, affecting its practical application. Therefore, simultaneously achieving a high iodine content, a high-load iodine cathode, and a high-utilization zinc anode is of great significance for promoting the practical application of zinc-iodine batteries. Summary of the Invention

[0004] To enhance the practical value of zinc-iodine batteries, this invention provides a universally applicable high-capacity iodine cathode and its preparation method (vacuum filtration + electrolyte permeation) to prepare a high-capacity iodine cathode without shuttle effect; at the same time, a thin zinc foil is used as the negative electrode, thereby achieving a high-utilization zinc negative electrode and a high-energy-density zinc-iodine battery.

[0005] In a first aspect, the present invention provides a high-loading composite iodine cathode based on MXene electrochemical reaction modifier, the high-loading composite iodine cathode comprising: a porous self-supporting composite electrode film formed by a mixture of MXene nanosheets, carbon materials, and cellulose, wherein the carbon materials are encapsulated in an MXene / cellulose network; and an iodine-active material loaded on the porous self-supporting composite electrode film; wherein the iodine-active material comprises I - Ions and I2; the MXene nanosheets are Ti3C2T x Nb2CT x Mo2CT x V2CT x At least one of them.

[0006] This invention relates to a three-dimensional (3D) interconnected self-supporting composite electrode membrane formed by the self-assembly of an electrochemical reaction modifier MXene, a physical adsorbent carbon material, and a binder cellulose. The high specific surface area of ​​the carbon material serves as a physical carrier for iodine-active species, while cellulose acts as a binder, enabling the MXene nanosheets and carbon material to self-assemble into the 3D interconnected self-supporting composite electrode membrane. The MXene nanosheet modifier enhances conductivity, improves the chemical anchoring ability of iodine species, and accelerates the kinetics of the iodine conversion reaction.

[0007] Preferably, the MXene loading on the high-load composite iodine cathode is 0.7–1.8 mg cm⁻¹. -2 The loading of the iodine-active substance is 10–25 mg / cm³. -2 .

[0008] Secondly, the present invention provides a method for preparing a high-loading composite iodine cathode based on MXene electrochemical reaction modifier, comprising: (1) Mix MXene nanosheets, carbon materials and cellulose to obtain a mixed dispersion; (2) The mixed dispersion was vacuum filtered and freeze-dried to obtain a self-supporting composite electrode membrane; (3) Using an aqueous solution containing iodine active substances as the positive electrode electrolyte, the solution is dropped onto the self-supporting composite electrode membrane and dried to obtain the high-load composite iodine positive electrode.

[0009] Preferably, the carbon material is at least one selected from activated carbon, carbon nanotubes, carbon fibers, and graphene; the cellulose is at least one selected from plant cellulose, bacterial cellulose, and microfibrillated cellulose. The carbon material has a high specific surface area and serves as a physical carrier for iodine-active species. The cellulose acts as a binder, enabling MXene nanosheets and the carbon material to self-assemble into a three-dimensionally (3D) interconnected, self-supporting composite electrode film.

[0010] Preferably, in step (1), the mass ratio of the MXene nanosheets, carbon material and cellulose binder is (0.1-2):(5-10):(0.1-1).

[0011] Preferably, in step (2), the freeze-drying temperature is -20 to -30°C and the time is 5 to 7 hours.

[0012] Preferably, the self-supporting composite electrode film is a porous self-supporting electrode formed by encapsulating carbon material in a highly conductive MXene / cellulose hybrid network formed by cellulose and MXene nanosheets.

[0013] Preferably, in step (3), the positive electrode electrolyte contains I - The concentration ratio of ions to I2 is (5-10):(1-5); The amount of positive electrolyte added to the self-supporting composite electrode membrane is determined according to the size and thickness of the self-supporting composite electrode membrane.

[0014] Preferably, in step (3), the drying is performed at room temperature for 6 to 20 hours.

[0015] Thirdly, the present invention provides a zinc-iodine battery, the zinc-iodine battery comprising the above-mentioned high-capacity composite iodine positive electrode, zinc negative electrode, battery separator, and electrolyte.

[0016] Preferably, the thickness of the zinc anode is 10–20 μm.

[0017] Preferably, the battery separator is at least one of glass fiber separator, aramid nanofiber separator, nonwoven fabric separator, filter paper separator, and polyolefin separator.

[0018] Preferably, the electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4; the concentration ratio of ZnSO4 to Li2SO4 in the electrolyte is (10-20):(1-5).

[0019] Beneficial effects: (1) The high-load composite iodine cathode prepared by the present invention can effectively suppress the shuttle effect of polyiodides and improve the kinetics of iodine conversion reaction; (2) The high iodine loading cathode prepared by this invention can establish strong chemical adsorption, and the loading of iodine active material is as high as 15.33-23 mg / cm³. -2 ; (3) The high iodine loading battery positive electrode prepared by the present invention and the 10-20 μm zinc foil are assembled into a zinc-iodine battery, which can reduce the corrosion of thin zinc negative electrode by polyiodides and achieve a stable high zinc negative electrode utilization rate and a high energy density zinc-iodine full cell. (4) The high-load composite iodine cathode based on MXene electrochemical reaction regulator provided by the present invention can be applied to zinc-iodine batteries, lithium-iodine batteries and other power and energy storage batteries. Attached Figure Description

[0020] Figure 1 The image shows a scanning electron microscope (SEM) image of the MX-AB electrode film prepared in Example 1. Figure 2 A digital photograph of the MX-AB electrode film prepared in Example 1; Figure 3 The weight changes of the MX-AB electrode film and MX-AB@I positive electrode film prepared in Example 1 before and after iodine loading; Figure 4 Thermogravimetric curves of the MX-AB electrode film and the MX-AB@I positive electrode film prepared in Example 1 before and after iodine loading; Figure 5 The image shows a cross-sectional SEM image and the corresponding elemental distribution image of the MX-AB@I cathode obtained in Example 1. Figure 6 This is a flowchart illustrating the preparation of the MX-AB@I cathode in Example 1; Figure 7 The image shows a SEM image of the AB electrode film prepared in Comparative Example 1. Figure 8 The conductivity of the MX-AB and AB electrode films prepared in Example 1 and Comparative Example 1, respectively; Figure 9 In-situ ultraviolet absorption spectroscopy of the "cube" zinc-iodine batteries assembled with the MX-AB@I and AB@I positive electrode films prepared in Example 1 and Comparative Example 1; Figure 10 Zinc-iodine batteries assembled with different iodine cathodes prepared in Example 1 and Comparative Examples 1-3 were tested at a current density of 0.1 A g. -1 Long cycle time and Coulomb efficiency; Figure 11 Zinc-iodine batteries assembled with MX-AB@I and AB@I cathodes prepared in Example 1 and Comparative Example 1 at 0.1 mV s -1 CV curve under the given conditions; Figure 12The zinc-iodine batteries assembled with 1.5x-MX-AB@I and 1.5x-AB@I cathodes prepared in Example 2 and Comparative Example 4 were tested at 0.1 A g. -1 Results of long-cycle testing under certain conditions. Detailed Implementation

[0021] To further illustrate the invention's content, features, and practical effects, the invention will be described in detail below with reference to embodiments. It should be noted that the modification methods of the invention are not limited to these specific implementation methods. Equivalent substitutions and modifications made by those skilled in the art based on their reading of the invention's content, without departing from the spirit and essence of the invention, are also within the scope of protection claimed by this invention.

[0022] In this invention, MXene nanosheets, carbon materials, and cellulose binder are blended and a self-supporting composite electrode membrane is obtained by vacuum filtration; iodine-active material I is introduced into the membrane via electrolyte permeation. - Ions and I2 are loaded onto the aforementioned self-supporting electrode membrane to obtain a high-load composite iodine cathode. This high-load composite iodine cathode effectively suppresses the shuttle effect of polyiodides and improves the kinetics of the iodine conversion reaction. In the preparation method of this invention, vacuum filtration allows for the control of membrane thickness through the concentration of the suspension, enabling efficient and uniform preparation of the electrode film. Electrolyte permeation is an effective iodine capture technique that loads iodine-active ions through impregnation.

[0023] In the method of loading active iodine ions using electrolyte permeation, iodine-active materials can be uniformly, rapidly, and effectively adsorbed onto the electrode. This method allows for precise control of the iodine loading on the electrode without causing loss of active material. Encapsulating iodine in an adsorbent membrane via melt diffusion, relying on the iodine sublimation phenomenon, is also a conventional strategy. However, in this process, iodine only binds to the adsorbate surface, and during subsequent charge-discharge tests, a large amount of iodine escapes through electrochemical reactions, leading to capacity loss. Therefore, achieving high iodine loading (greater than 5 mg / cm³) requires further research. -2 In the preparation of positive electrodes, the electrolyte permeation method is irreplaceable.

[0024] In this invention, the combination of vacuum filtration and electrolyte permeation significantly reduces preparation time and improves efficiency. More importantly, the iodine-loaded membrane prepared by vacuum filtration has a considerable specific surface area, providing abundant adsorption sites for iodine loading via electrolyte permeation, thus achieving a stable high-iodine-loaded cathode.

[0025] In this invention, MXene is a novel two-dimensional material with a layered structure, a large number of active metal atoms, and abundant polar surface functional groups. The titanium metal center in the MXene electrochemical reaction modifier functions as a Lewis acid site, enabling it to establish a strong chemisorption with polyiodide anions (Lewis bases), thereby effectively immobilizing the polyiodides on the positive electrode and suppressing their shuttle effect. Furthermore, due to its electronic conductivity and catalytic activity, the MXene electrochemical reaction modifier can reduce the I₂ / I₂ ratio. - The overpotential and activation energy barrier during the conversion process can significantly improve the kinetics of the iodine conversion reaction. Furthermore, the strong chemisorption and kinetic-promoting properties of MXene electrochemical reaction modifier can also reduce the corrosion of the thin zinc anode by polyiodides, thereby improving its reversibility and achieving a stable zinc-iodine full cell with high zinc anode utilization and high energy density.

[0026] In this invention, a flexible electrode obtained by mixing MXene nanosheets, carbon materials, and cellulose and then vacuum filtration serves as a carrier membrane for the iodine-active material. The MXene in this invention not only provides high conductivity and improves the iodine conversion kinetics, but also adsorbs the iodine-active material through chemical action, increasing the iodine loading and suppressing the shuttle effect. Therefore, in the high-load iodine cathode provided by this study, the MXene electrochemical reaction modulator, through the synergistic effect of high conductivity and chemical adsorption, solves the problems of slow kinetics and multiple iodide shuttle in high-load zinc-iodine batteries, which is of great significance for the practical development of zinc-iodine batteries.

[0027] The following exemplarily illustrates the preparation method of the high-loading composite iodine cathode based on MXene electrochemical reaction modifier provided by the present invention (e.g. Figure 6 (As shown).

[0028] Preparation of MXene nanosheets. The MXene nanosheets in this invention can be produced using fluorine-containing etching (Naguib M, Kurtoglu M, Presser V, Lu J, Niu J, Heon M, Hultman L, Gogotsi Y, Barsoum MW. Two-dimensional nanocrystals produced by exfoliation of Ti3AlC2. Adv Mater. 2011 Oct4; 23(37):4248-53.), electrochemical etching (Yang S, Zhang P, Wang F, Ricciardulli AG, Lohe MR, Blom PWM, Feng X. Fluoride-Free Synthesis of Two-Dimensional Titanium Carbide (MXene) Using A Binary Aqueous System. Angew ChemInt Ed Engl. 2018 Nov 19; 57(47):15491-15495.), and alkaline etching (Li T, Yao L, Liu Q, Gu J, Luo R, Li J, Yan X, Wang W, Liu P, Chen B, Zhang W, Abbas W, Naz R, Zhang D. Fluorine-Free Synthesis of High-Purity Ti3C2T x MXene nanosheets were prepared by methods such as (T=OH,O)via Alkali Treatment. Angew ChemInt Ed Engl. 2018 May 22;57(21):6115-6119.), molten salt etching (Ghidiu M, Lukatskaya MR, Zhao MQ, Gogotsi Y, Barsoum MW. Conductive two-dimensional titanium carbide 'clay' with high volumetric capacitance. Nature. 2014 Dec 4;516(7529):78-81.). As an example, 1g of lithium fluoride was dissolved in 15mL of 9M hydrochloric acid, and 1g of MXene precursor (Ti3AlC2) powder was slowly added. After etching at 40℃ for 48 hours, the nanosheets were obtained by centrifugation and washing 6 times. x Suspension; then, multilayer Ti3C2T xThe suspension was dispersed in 50 mL of deionized water and sonicated for 60 min. Finally, after centrifugation for 40 min, the dark green supernatant was collected to obtain a few-layer Ti3C2T. x MXene nanosheets.

[0029] MXene nanosheets, carbon materials, and cellulose binders were mixed to obtain a mixed dispersion.

[0030] In an optional embodiment, the MXene nanosheets are Ti3C2T. x Nb2CT x Mo2CT x V2CT x At least one of the following. The carbon material is at least one of activated carbon, carbon nanotubes, carbon fibers, and graphene. The cellulose binder is at least one of plant cellulose, bacterial cellulose, and microfibrillated cellulose.

[0031] In an optional embodiment, the mass ratio of the MXene nanosheets, carbon material, and cellulose binder is (0.1–2):(5–10):(0.1–1), for example, 1:8:0.85. If the content of MXene nanosheets is too low, it cannot adsorb enough polyiodides, causing the polyiodides to still exhibit a shuttle effect; if the content of MXene nanosheets is too high, the adsorption force on iodine is too strong, and some iodine will lose its activity due to adsorption.

[0032] The mixed dispersion was vacuum filtered and freeze-dried, and then cut by a slicer to obtain a self-supporting composite electrode membrane.

[0033] The high-load composite iodine positive electrode is obtained by drop-adding a positive electrolyte onto the self-supporting composite electrode membrane using an electrolyte permeation method. Specifically, an aqueous solution containing iodine-active substances is used as the positive electrolyte, which is drop-added onto the self-supporting composite electrode membrane and dried to obtain the high-load composite iodine positive electrode.

[0034] In an optional embodiment, in the electrolyte, I - The concentration ratio of ions to I2 is (5-10):(1-5). The amount of electrolyte used is determined based on the size and thickness of the self-supporting composite electrode membrane.

[0035] In an optional embodiment, the drying is performed at room temperature for 6 to 20 hours.

[0036] The high-load composite iodine cathode prepared by this invention has an MXene loading of 0.7–1.8 mg / cm³. -2 The loading of iodine-active substances is 10–25 mg / cm³. -2 .

[0037] In addition, the present invention also provides a zinc-iodine battery, which includes the above-mentioned high-capacity composite iodine positive electrode, zinc negative electrode, battery separator, and electrolyte.

[0038] In an optional embodiment, the thickness of the zinc negative electrode is 10–20 μm. As an example, a zinc sheet with a thickness of 10–20 μm is taken, polished, and then cut into a negative electrode sheet.

[0039] In an optional embodiment, the battery separator is at least one of glass fiber separator and aramid nanofiber separator.

[0040] In an optional embodiment, the electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4.

[0041] The following exemplarily illustrates the assembly method of the zinc-iodine battery provided by the present invention.

[0042] Zinc sulfate and lithium sulfate were dissolved in deionized water and stirred to prepare a mixed electrolyte of ZnSO4 and Li2SO4; the positive electrode, negative electrode, electrolyte and battery separator were assembled into a zinc-iodine battery.

[0043] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0044] Example 1

[0045] The preparation process of the high-loading composite iodine cathode based on MXene electrochemical reaction modifier in Example 1 includes: (1) dissolving 1g of lithium fluoride in 15mL of 9M hydrochloric acid, slowly adding 1g of MXene precursor (Ti3AlC2) powder, etching at 40℃ for 48 hours, and then washing by centrifugation 6 times to obtain multilayer Ti3C2T x Suspension. Then multilayer Ti3C2T x The suspension was dispersed in 50 mL of deionized water and sonicated for 60 min. Finally, after centrifugation for another 40 min, the dark green supernatant was collected to obtain a few-layer Ti3C2T. x MXene nanosheets; (2) At room temperature, 12.56 mg MXene and 10.76 mg nano-bacterial cellulose were dispersed in 20 mL of water and magnetically stirred for 30 min to form a slurry linked by hydrogen bonds. Subsequently, 100 mg of activated carbon particles were added to the resulting slurry and stirred for another 24 hours to obtain a composite electrode slurry (referred to as MX-AB). The MX-AB slurry was filtered onto a filter membrane using vacuum filtration technology, freeze-dried, and then cut into 1.13 cm² pieces using a slicer. 2 MX-AB electrode film; (3) Using an aqueous solution containing 2M LiI and 0.2M I2 as the positive electrode electrolyte, 56.76 μL of the positive electrode electrolyte was dropped onto the MX-AB electrode film and dried at room temperature for 6 h to obtain a high-load composite iodine positive electrode (MX-AB@I).

[0046] Assembly of an aqueous zinc-iodine battery: The obtained MX-AB@I was used as the iodine positive electrode, 30μL of 2M ZnSO4 + 0.1M Li2SO4 solution was used as the electrolyte, a 20μm metallic zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0047] Example 2

[0048] The preparation process of the high-loading composite iodine cathode based on MXene electrochemical reaction modifier in Example 2 includes: (1) dissolving 1g of lithium fluoride in 15mL of 9M hydrochloric acid, slowly adding 1g of MXene precursor (Ti3AlC2) powder, etching at 40℃ for 48 hours, and then washing by centrifugation 6 times to obtain multilayer Ti3C2T x Suspension. Then multilayer Ti3C2T x The suspension was dispersed in 50 mL of deionized water and sonicated for 60 min. Finally, after centrifugation for another 40 min, the dark green supernatant was collected to obtain a few-layer Ti3C2T. x MXene nanosheets; (2) At room temperature, 18.84 mg MXene and 16.14 mg nano-bacterial cellulose were dispersed in 20 mL of water and magnetically stirred for 30 min to form a slurry linked by hydrogen bonds. Subsequently, 150 mg of activated carbon particles were added to the resulting slurry and stirred for another 24 hours to obtain a composite electrode slurry (referred to as 1.5x-MX-AB). The 1.5x-MX-AB slurry was filtered onto a filter membrane using vacuum filtration technology, freeze-dried, and then cut into 1.13 cm² pieces using a slicer. 2 1.5x-MX-AB electrode film; (3) Using an aqueous solution containing 2M LiI and 0.2M I2 as the positive electrode electrolyte, 85.14 μL of the positive electrode electrolyte was dropped onto a 1.5x-MX-AB electrode membrane. After drying at room temperature for 6 h, a high iodine loading of 23 mg cm⁻¹ was obtained. -2 The composite iodine cathode (1.5x-MX-AB@I).

[0049] Assembly of an aqueous zinc-iodine battery: The obtained 1.5x-MX-AB@I was used as the iodine positive electrode, 30μL of 2M ZnSO4 + 0.1M Li2SO4 solution was used as the electrolyte, a 10μm metallic zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0050] Comparative Example 1

[0051] The preparation method of the high-load composite iodine cathode in Comparative Example 1 is the same as that in Example 1, except that: in step (2), the amount of MXene used is 0 mg, and the AB electrode membrane is prepared; then, using an aqueous solution containing 2M LiI and 0.2M I2 as the cathode electrolyte, 56.76 μL of cathode electrolyte is dropped onto the AB electrode membrane, and after drying at room temperature for 6 h, the high-load iodine cathode (AB@I) is obtained.

[0052] Comparative Example 2

[0053] The preparation method of the high-load composite iodine cathode in Comparative Example 2 is the same as that in Example 1, except that in step (2), the amount of MXene used is 6.28 mg, and a 0.5MX-AB electrode film is prepared; then, using an aqueous solution containing 2M LiI and 0.2M I2 as the cathode electrolyte, 56.76 μL of cathode electrolyte is dropped onto the 0.5MX-AB electrode film, and after drying at room temperature for 6 h, a high-load composite iodine cathode (0.5MX-AB@I) is obtained.

[0054] Assembly of an aqueous zinc-iodine battery: The obtained 0.5MX-AB@I was used as the iodine positive electrode, 30μL of 2M ZnSO4 + 0.1M Li2SO4 solution was used as the electrolyte, a 20μm metallic zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the battery separator to assemble an aqueous zinc-iodine battery.

[0055] Comparative Example 3

[0056] The preparation method of the high-load composite iodine cathode in Comparative Example 3 is the same as that in Example 1, except that in step (2), the amount of MXene used is 25.12 mg, and a 2MX-AB electrode membrane is prepared. Subsequently, using an aqueous solution containing 2M LiI and 0.2M I2 as the cathode electrolyte, 56.76 μL of cathode electrolyte is dropped onto the 2MX-AB electrode membrane, and after drying at room temperature for 6 h, a high-load composite iodine cathode (2MX-AB@I) is obtained.

[0057] Assembly of an aqueous zinc-iodine battery: The obtained 2MX-AB@I was used as the iodine positive electrode, 30μL of 2M ZnSO4 + 0.1M Li2SO4 solution was used as the electrolyte, a 20μm metallic zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0058] Comparative Example 4

[0059] The preparation method of the high-load composite iodine cathode in Comparative Example 4 is the same as that in Example 2, except that in step (2), the amount of MXene used is 0 mg, and a 1.5x-AB electrode film is prepared; then, an aqueous solution containing 2M LiI and 0.2M I2 is used as the cathode electrolyte, and 85.14 μL of cathode electrolyte is dropped onto the 1.5x-AB electrode film. After drying at room temperature for 6 h, a high-load iodine cathode (1.5x-AB@I) is obtained.

[0060] Assembly of an aqueous zinc-iodine battery: The obtained 1.5x-AB@I was used as the iodine positive electrode, 30μL of 2M ZnSO4 + 0.1M Li2SO4 solution was used as the electrolyte, a 10μm metallic zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0061] Figure 1 This is a scanning electron microscope (SEM) image of the MX-AB electrode film prepared in Example 1. Figure 2 This is a digital photograph of the MX-AB electrode film prepared in Example 1. Figure 1 It is known that the MX-AB electrode film is a porous, self-supporting electrode formed by uniformly encapsulating activated carbon particles in a highly conductive MXene / bacterial cellulose hybrid network formed by nanofibers and MXene nanosheets. Furthermore, [the text abruptly ends here, likely due to an incomplete sentence or missing information]. Figure 2 It is known that the stable interconnection between each component gives the MX-AB electrode good mechanical flexibility, enabling it to bend without breaking.

[0062] Figure 3 The weight changes of the MX-AB electrode film and MX-AB@I positive electrode film prepared in Example 1 before and after iodine loading. Figure 4 The thermogravimetric curves of the MX-AB electrode film and the MX-AB@I positive electrode film prepared in Example 1 before and after iodine loading are shown. Figure 3 It can be seen that the actual iodine active material loading of the high-load MX-AB@I cathode is approximately 15.33 mg cm⁻¹. -2 This is consistent with the theoretically calculated iodine loading (15.35 mg cm⁻¹). -2 Very close. And by Figure 3 It can be seen that the iodine active material content of the self-supporting MX-AB@I cathode is as high as approximately 60.43 wt.%.

[0063] Figure 5 The image shows a cross-sectional SEM image and corresponding elemental distribution of the MX-AB@I cathode prepared in Example 1. As can be seen from the image, the thickness of the high-iodine-loaded MX-AB@I cathode is approximately 270 μm. The C, Ti, and I elemental distribution maps further confirm the successful loading of iodine in the cathode and the uniform distribution of each element.

[0064] Figure 7 The image shows a SEM image of the AB electrode membrane prepared in Comparative Example 1. As can be seen from the image, the AB electrode membrane in Comparative Example 2 exhibits a porous network structure formed by nano-bacterial cellulose binding activated carbon particles.

[0065] Figure 8 The figures show the conductivity of the MX-AB and AB electrode films prepared in Example 1 and Comparative Example 1, respectively. As can be seen from the figures, the MX-AB electrode film prepared in Example 1 achieved a conductivity as high as ~13.57 S cm⁻¹. -1 The high conductivity of the AB electrode film prepared in Comparative Example 1 is compared to that of the AB electrode film prepared in Comparative Example 1, which has a conductivity of only about 3.66 S cm⁻¹. -1 As can be seen from the SEM images of the MX-AB electrode in Example 1 and the AB electrode film in Comparative Example 1, this is due to the Ti3C2T adhering to the nano-bacterial cellulose in the MX-AB electrode film prepared in Example 1. x MXene nanosheets act as fast and continuous electron transport pathways, enhancing the conductive contact between activated carbon particles and thus improving the overall conductivity of the composite electrode.

[0066] Combining the battery working principle with the ultraviolet-visible absorption spectroscopy testing device, the iodine cathodes of Example 1 and Comparative Example 1 were designed as "cuvette" type batteries to compare the immobilization effects of the MX-AB@I cathode in Example 1 and the AB@I cathode in Comparative Example 1 on polyiodides.

[0067] Figure 9 In-situ UV absorption spectroscopy measurements were performed on the "cube" zinc-iodine batteries assembled with the MX-AB@I and AB@I positive electrode films prepared in Example 1 and Comparative Example 1. Figure 9 As shown in Figure a, an iodine-loaded composite positive electrode (MX-AB@I or AB@I) and a zinc metal negative electrode are placed at opposite ends of a cuvette-type battery, using a 2M ZnSO4 + 0.1M Li2SO4 mixed solution as the electrolyte. The positive and negative electrodes of the cuvette-type battery are connected to an electrochemical workstation via wires. Ultraviolet or visible light is transmitted through the other two sides of the cuvette to measure the real-time concentration of polyiodides during charging. Figure 9 As shown in b, the zinc-iodine battery using the AB@I cathode in Comparison 1 shows increased absorbance at 288 and 354 nm, indicating that I3... -The concentration increases rapidly. This is due to the weak interaction between activated carbon and polyiodides, which makes the polyiodides readily soluble in the electrolyte, thus increasing the peak value in the UV-Vis absorption spectroscopy measurement. However, in the zinc-iodine battery using the MX-AB@I cathode in Example 1, the concentration of I3... - The relevant absorption peak values ​​remained at a low level throughout the charging process (e.g. Figure 9 (As shown in c). Therefore, in-situ UV-Vis absorption spectroscopy measurements confirm the effectiveness of the MXene-functionalized composite electrode for I3. - The immobilization and adsorption of intermediate products can effectively suppress the shuttle effect of polyiodide ions.

[0068] The electrochemical performance of the aqueous zinc-iodine batteries prepared in Example 1 and Comparative Examples 1-3 of this invention was tested.

[0069] Under the same high iodine loading, through coulombic efficiency ( Figure 10 (as shown in the image above) and loop testing ( Figure 10 The following figure (in which the cycle life and reversibility of zinc-iodine batteries prepared with different iodine cathodes in Example 1 and Comparative Examples 1-3 of this invention are analyzed to directly reflect the multiiodine ion shuttle effect. Figure 10 Zinc-iodine batteries assembled with different iodine cathodes prepared in Example 1 and Comparative Examples 1-3 were tested at a current density of 0.1 Ag. -1 The zinc-iodine battery assembled with the iodine cathode (AB@I) in Comparative Example 1, without MXene, rapidly decayed after only 40 cycles, exhibiting a low average coulombic efficiency of 91.04%, indicating a severe polyiodide shuttle effect. In contrast, the zinc-iodine battery assembled with the iodine cathode (0.5MX-AB@I) in Comparative Example 2 only began to fail after 160 cycles, with an average coulombic efficiency of 96.84%. However, due to the low MXene content, insufficient polyiodide adsorption resulted in continued polyiodide shuttle effect. Furthermore, the zinc-iodine battery assembled with the iodine cathode (MX-AB@I) in Example 1 and the zinc-iodine battery assembled with the iodine cathode (2MX-AB@I) in Comparative Example 3 achieved a cycle life of 260 cycles, with average coulombic efficiencies of 97.23% and 97.14%, respectively, and capacity retention rates of 95.65% and 92.67%, respectively, demonstrating excellent performance in suppressing polyiodide shuttle. The rapid capacity decay of the iodine cathode (2MX-AB@I) in Comparative Example 3 may be due to the excessively high MXene content leading to strong adsorption of iodine, causing some iodine to lose its activity through adsorption. Therefore, both excessively high and low MXene content will reduce the overall performance of the battery. In the iodine cathode (MX-AB@I) of Example 1 of this invention, the MXene content is 1 mg cm⁻¹. -2 The battery exhibits the best cycle stability under these conditions.

[0070] The redox kinetics of zinc-iodine batteries were evaluated by cyclic voltammetry (CV) using the iodine cathodes prepared in Example 1 and Comparative Example 1 of this invention. Figure 11 Zinc-iodine batteries assembled with MX-AB@I and AB@I cathodes prepared in Example 1 and Comparative Example 1 at 0.1 mV s -1 CV curves under the given conditions. Both batteries show a pair of redox peaks, indicating I2 / I... - The redox reaction. Compared with the iodine cathode AB@I zinc-iodine battery prepared in Comparative Example 1, the iodine cathode MX-AB@I zinc-iodine battery prepared in Example 1 of this invention has a sharper redox peak and a higher peak current density. In addition, the polarization overpotential of the MX-AB@I zinc-iodine battery is significantly lower than that of the AB@I zinc-iodine battery (124mV vs. 182mV), indicating that Ti3C2T x MXene electrochemical reaction modifiers enhance the redox kinetics of zinc-iodine batteries.

[0071] The electrochemical performance of the aqueous zinc-iodine batteries prepared in Example 2 and Comparative Example 4 of this invention was tested.

[0072] Figure 12 The zinc-iodine batteries assembled with 1.5x-MX-AB@I and 1.5x-AB@I cathodes prepared in Example 2 and Comparative Example 4 were tested at 0.1 A g. -1 The results of long-cycle testing under the specified conditions are shown in the figure. As can be seen from the figure, the zinc-iodine battery assembled using the iodine cathode (1.5x-MX-AB@I) in Example 2 of this invention achieves a long-cycle test performance of 2.3 mA cm⁻¹. -2 Achieving approximately 4.0 mAh cm⁻¹ under these conditions -2 High areal specific capacity. Even after 200 cycles, it still retains approximately 94.4% of its initial capacity (3.77 mAh cm⁻¹). -2 In contrast, the zinc-iodine battery assembled using the iodine cathode (1.5x-AB@I) of Comparative Example 4 showed significantly reduced durability, with a capacity retention of only 32.9% after 58 cycles under the same conditions.

[0073] More importantly, the zinc-iodine battery assembled using the iodine cathode (1.5x-MX-AB@I) in Example 2 of this invention achieves a zinc utilization rate of 78.7% and a power output of 171.3 Wh / kg. -1 High energy density.

[0074] In summary, the high iodine loading iodine cathode provided by this invention solves the problems of slow kinetics and multiple iodide shuttle in high-loading zinc-iodine batteries by introducing the MXene electrochemical reaction regulator, which is of great significance for improving the performance and practical application of zinc-iodine batteries.

Claims

1. A high-loading composite iodine cathode based on MXene electrochemical reaction modifier, characterized in that, The high-load composite iodine cathode comprises: a porous self-supporting composite electrode membrane formed by the self-assembly of MXene nanosheets, carbon materials, and cellulose through an MXene / cellulose network, encapsulating the carbon materials; and an iodine-active material loaded onto the porous self-supporting composite electrode membrane via an electrolyte permeation method; wherein the iodine-active material comprises I... - And I2, wherein the loading of the iodine-active substance is 10–25 mg cm⁻¹ -2 The electrolyte permeation method includes: using an iodine-containing active substance I... - An aqueous solution of I₂ was used as the positive electrode electrolyte and added dropwise onto the self-supporting composite electrode membrane. After drying, the high-load composite iodine positive electrode was obtained; in the positive electrode electrolyte, I₂... - The concentration ratio of I2 to I2 is (5-10):(1-5); The MXene nanosheets are Ti3C2T x Nb2CT x Mo2CT x V2CT x At least one of them.

2. The high-loading composite iodine cathode based on MXene electrochemical reaction modifier according to claim 1, characterized in that, The MXene loading on the high-load composite iodine cathode is 0.7–1.8 mg / cm³. -2 .

3. A method for preparing a high-loading composite iodine cathode based on MXene electrochemical reaction modifier according to claim 1 or 2, characterized in that, include: (1) Mix MXene nanosheets, carbon materials and cellulose to obtain a mixed dispersion; (2) The mixed dispersion was vacuum filtered and freeze-dried to obtain a self-supporting composite electrode membrane; (3) Using an aqueous solution containing iodine active material as the positive electrode electrolyte, the solution is dropped onto the self-supporting composite electrode membrane and dried to obtain the high-load composite iodine positive electrode.

4. The preparation method according to claim 3, characterized in that, The carbon material is at least one of activated carbon, carbon nanotubes, carbon fibers, and graphene; The cellulose is at least one of plant cellulose and bacterial cellulose.

5. The preparation method according to claim 3 or 4, characterized in that, In step (1), the mass ratio of MXene nanosheets, carbon materials and cellulose is (0.1-2):(5-10):(0.1-1).

6. The preparation method according to claim 3, characterized in that, In step (2), the freeze-drying temperature is -20 to -30°C and the time is 5 to 7 hours.

7. The preparation method according to claim 3, characterized in that, In step (3), the drying is carried out at room temperature for 6 to 20 hours.

8. A zinc-iodine battery, characterized in that, The zinc-iodine battery comprises the high-load composite iodine cathode based on MXene electrochemical reaction modifier as described in claim 1 or 2, a zinc anode, a battery separator, and an electrolyte.

9. The zinc-iodine battery according to claim 8, characterized in that, The thickness of the zinc negative electrode is 10–20 μm; The battery separator is at least one of glass fiber separator, aramid nanofiber separator, and polyolefin separator; The electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4; the concentration ratio of ZnSO4 to Li2SO4 in the electrolyte is (10-20):(1-5).

Citation Information

Patent Citations

  • High-stability zinc-iodine battery positive electrode composite material as well as preparation method and application thereof

    CN113036144A

  • Preparation method of MXene nanocellulose carbon nanotube composite material

    CN114605708A